2018
DOI: 10.1183/13993003.01812-2017
|View full text |Cite
|
Sign up to set email alerts
|

Relative and absolute lung function change in a general population aged 60–102 years

Abstract: Data on longitudinal lung function change in the elderly are scarce. Uncertainty remains about whether to use absolute or relative change and how it relates to subject demographics.We studied absolute and relative forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC) change in a population-based geriatric sample using a repeated measurements model adjusted for age, sex, smoking habits, heart failure, hypertension, diabetes, coronary heart disease, educational level, occupation, alcohol consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 50 publications
3
32
2
1
Order By: Relevance
“…In Triebner et al ,32 obese individuals reported greater declines of FEV 1 (29 mL/year) and FVC (25 mL/year) compared with individuals with normal BMI (FEV 1 22 mL/year, FVC 10 mL/year). In Luoto et al ,35 having a BMI greater than 35 was significantly associated with a slower decline of FEV 1 (32 mL/year compared with 46 mL/year, p=0.04), but it did not significantly affect FVC decline.…”
Section: Resultsmentioning
confidence: 84%
“…In Triebner et al ,32 obese individuals reported greater declines of FEV 1 (29 mL/year) and FVC (25 mL/year) compared with individuals with normal BMI (FEV 1 22 mL/year, FVC 10 mL/year). In Luoto et al ,35 having a BMI greater than 35 was significantly associated with a slower decline of FEV 1 (32 mL/year compared with 46 mL/year, p=0.04), but it did not significantly affect FVC decline.…”
Section: Resultsmentioning
confidence: 84%
“…However, these studies were carried out in the general population; only 50% had a smoking history, and the presence of respiratory symptoms was not specified. 8,29 In contrast, in our study, performed carried out in a population of similar age, all patients had a smoking history, and 97% were symptomatic at inclusion. We believe that in these patients the obstruction measured with FR strongly suggests the presence of disease.…”
Section: Discussionmentioning
confidence: 60%
“…This is consistent with previous studies that found no association between smoking status and rate of FVC decline in the general population and in COPD populations. 19,38,39 ICS Interestingly, we found that patients on ICS-containing medications were more likely to have accelerated FEV 1 decline. Many RCTs have investigated the relationship between ICS and lung function in COPD and results have shown that patients on ICS have attenuated rate of FEV 1 decline compared to non-ICS treatments.…”
Section: Characteristics Associated With Accelerated Lung Function Dementioning
confidence: 65%
“…17,18 FVC has been described longitudinally in populations without COPD but the rate of FVC decline in COPD patients is poorly described. [19][20][21][22] The rate of lung function decline in a generalizable population of average, "real world" COPD patients who would be seen in primary care has not been described. In addition, few studies have looked at how comorbidities, as well as other clinical characteristics such as medication, symptoms, and patient demographics, influence the rate of lung function decline, as measured by both FEV 1 and FVC in COPD patients in primary care.…”
Section: Introductionmentioning
confidence: 99%